2020
DOI: 10.3390/molecules26010116
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Assessment Resulting from Sediment Contamination with Perfluoroalkyl Substances

Abstract: Due to wide use of perfluoroalkyl substances (PFASs) (e.g., in metal-plating, in fire-fighting foam, lubricants) and their resistance to degradation, they occur widely in the environment. The aim of this study was to estimate the environmental risk resulting from the presence of PFASs in the Gulf of Gdansk. Therefore, 17 PFASs concentrations were determined using ultra performance liquid chromatography with tandem mass spectrometry detection (UPLC-MS/MS). Additionally, sediment ecotoxicity was investigated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…There are many environmental studies in which multivariate statistical methods were used, for instance, physicochemical analysis of surface waters [34,37,39], waters in retention reservoirs [36], bottom sediments [48,49] and atmospheric air [31,50], as well as the assessment of the microbiological quality of air [3,33,38]. In our current study, the multivariate data analysis with the use of contingency tables showed a statistically significant relationship between the number of molds and yeast-like fungi in the coastal towns in 2014-2017 and 2018.…”
Section: Discussionmentioning
confidence: 99%
“…There are many environmental studies in which multivariate statistical methods were used, for instance, physicochemical analysis of surface waters [34,37,39], waters in retention reservoirs [36], bottom sediments [48,49] and atmospheric air [31,50], as well as the assessment of the microbiological quality of air [3,33,38]. In our current study, the multivariate data analysis with the use of contingency tables showed a statistically significant relationship between the number of molds and yeast-like fungi in the coastal towns in 2014-2017 and 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of 17 per- and polyfluoroalkyl substances (PFASs), as representatives of emerging contaminants in the Gulf of Gdansk, are discussed in the paper of Gałęzowska et al [ 16 ]. Due to wide use of PFASs (e.g., in metal-plating, in fire-fighting foam, lubricants) and their resistance to degradation, they occur widely in the environment.…”
mentioning
confidence: 99%